Fundamental study on development of the biological artificial liver using biomatrix as a culture substrate - 田辺 高由; 少出 典男; 治徳 通博; 近藤 英明; 小野 良策; 長島 秀夫; 森 将晏 (Jinko Zoki, 1985)
Extracellular matrices of various organs were prepared and utilized for the culture substrate of the hepatocytes in the primary culture, with an aim of establishing biological artificial-liver support. Isolated rat hepatocytes attached the extracellular matrix of the liver “liver biomatrix” more rapidly than those of spleen and lung. Cells attached liver biomatrix started spreading immediately after attachment under cooperation with some serum factors, but cells with no contact to the matrix did not during the first 30 minutes of cell seeding. Cell attachment and spreading did not show any differences in between intra- and interlobular matrices of the liver also in blockade of fibronectin and laminin with the respective antibodies. These results indicated that the extracellular matrix of the liver had an organ specific ability of hepatocyte attachment and spreading. 培養肝細胞を用いた生物学的人工肝作製を目的として, 肝より細胞外間質物質(Biomatrix)を調整し, これとラット灌流肝細胞の相互作用に関する基礎的研究を行い, その培養基質としての有用性を検討した。肝Biomatrixは, ラットおよびヒト正常肝より小葉内間質物質と小葉間間質物質とに分画調製した。前者は格子線維が主体であり, 後者はCollagen, 弾力, 筋線維が混在していた。ラット灌流肝細胞は, ラット, ヒト肝Biomatrixのいずれの分画にもほぼ等しく良好に生着した。他臓器Biomatrixとの比較では, 肝, 脾, 肺の順に良好な生着がみられた。肝Biomatrixに対する生着は, Fibronectin抗体, Laminin抗体のいずれにも阻害されなかった。ラット肝Biematrix上の肝細胞は, 1週間後もAlbumin, Transferrin, C3,: Fibrinogenの分泌能を維持した。肝Biomatrix上で24時間培養した肝細胞を, Trypsin EGTAで処理したところ, ラット肝Biomatrixでは接着が強く, ヒトに比し遊離が遅延した。